How to align organizational culture with corporate goals: a study on a large-sized Brazilian engineering company - Seixas, Maria Augusta de Castro; Andrade, Emmanuel Paiva de; Cândido, João Carlos; Pizzol, Rosa Amélia (Brazilian Journal of Operations & Production Management, 2020)
Goal: What a company produces and how it does is permeated by belief, thought and shared feelings in the employees. The goal of this study is to construct an explanation on how this phenomenon manifests itself in an engineering company. Design / Methodology / Approach: The qualitative approach was adequate to understand how elements of individual narratives were related to the company culture. The analytical procedures were based on the systematics of Grounded Theory. Texts written in 2016 by the employees about their work for applying for a knowledge management program within their company were the source of this corpus. Results: The interpretation of the data has shown that four aspects form sets of filters that construct the culture, in a non-homogeneous learning process. In the intersection of these sets we can find essential values that motivate the employees of different positions, activities, regions, genders and ages. Limitations of the investigation: The knowledge management program asked for overcoming stories which is a limiting factor since employees have chosen successful stories from their work to tell. Practical implications: The findings allow us to infer that changing or reinforcing the current values implies the promotion of action that permeates these filters and are simultaneously not in the purview of the company’s management. Originality / Value: The study also pointed out the pertinence of the use of storytelling for knowing the actors’ interpretation about the values of the organization.